Gli aiuti internazionali: l'alternativa più facile. (Foreign aid – the soft option) - P.T. BAUER; J.B. WOOD (Moneta e Credito, 2014)
The article examines a number of issues regarding the merits of foreign aid as an instrument for the development of backward countries that have yet to receive adequate attention. The author argues that Foreign aid has obscured the deep seated factors beneath differences in prosperity and that economic development requires cultural change in the backward countries and structural changes in the advanced countries. Furthermore, it is argued that foreign aid leads to an ineffective use of the world’s supplies of capital and promotes concentration of power both in the rich and poor countries. Finally, some other ways to encourage economic development in the backwards countries are explored.